Perancangan Dan Implementasi Sistem Pakar Diagnosis Pertolongan Pertama Penyakit Akibat Gigitan Nyamuk Menggunakan Metode Certainty Factor Berbasis Android - Abdi Pandu Kusuma; Agung Sugiarto (Jurnal Teknika, 2020)
Mosquitoes are insects that often make us worried because of the bite. One of the dangers caused by mosquito bites is a variety of diseases that can even cause death. Indonesia is a tropical country that is endemic in diseases that are spread by mosquitoes, such as dengue fever, malaria, and filariasis (elephantiasis). The expert system of first aid diagnosis of diseases caused by mosquito bites will be an alternative to overcome the problems that occur so that later the public can find out about information and do first aid to diseases caused by mosquito bites. This system was built using the Certainty Factor method and implemented into an Android-based application to determine the type of disease suffered due to mosquito bites. Knowledgebase was obtained from interviews with Dr. Andik Setiawan, literature study, and browsing. The results of testing the expert system of first aid diagnosis of diseases caused by mosquito bites is known that the Certainty Factor method is able to determine the type of disease from the symptoms mentioned by 40.8%.